2013
DOI: 10.1371/journal.pone.0058579
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Cell Phone Conversations on the Attention and Memory of Bystanders

Abstract: The pervasive use of cell phones impacts many people–both cell phone users and bystanders exposed to conversations. This study examined the effects of overhearing a one-sided (cell phone) conversation versus a two-sided conversation on attention and memory. In our realistic design, participants were led to believe they were participating in a study examining the relationship between anagrams and reading comprehension. While the participant was completing an anagram task, the researcher left the room and partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
15
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 37 publications
2
15
1
Order By: Relevance
“…The finding that dialogues are more disruptive than halfalogues runs contrary to what was found in Emberson et al (), Galván et al () and Norman and Bennett (). One possible explanation for the difference in results between these extant studies and the current study may be found in the task the participants conducted.…”
Section: Discussioncontrasting
confidence: 87%
See 1 more Smart Citation
“…The finding that dialogues are more disruptive than halfalogues runs contrary to what was found in Emberson et al (), Galván et al () and Norman and Bennett (). One possible explanation for the difference in results between these extant studies and the current study may be found in the task the participants conducted.…”
Section: Discussioncontrasting
confidence: 87%
“…As dialogues overall contain more semantic information than halfalogues, and the speech stream unfolds during a more steady pace over time, a straightforward hypothesis would be that dialogues are more disruptive than halfalogues. However, Norman and Bennett (), Galván, Vessal and Golley () and Emberson, Lupyan, Goldstein and Spivey () exposed their participants to halfalogues and dialogues while the participants were conducting an anagram task (Galván et al, ), a reaction time task and a visual monitoring task (Emberson et al, ) or no task at all (Norman & Bennett, ). Self‐rating measures of annoyance and distraction in these studies suggested, perhaps counterintuitively, that halfalogues are more disruptive than dialogues.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, several objective measures have reinforced these subjective ratings: Cognitive performance is differentially affected by halfalogues and dialogues. For example, Emberson, Lupyan, Goldstein, and Spivey (2010; see also Galván, Vessal, & Golley, 2013) found that ignoring a 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 Telephone Distraction 4 halfalogue as compared with a dialogue disrupted performance on a visual monitoring (tracking) task and a choice reaction task.…”
mentioning
confidence: 99%
“…Moreover, cognitive performance Background Speech Impairs Face Memory 4 can be differentially affected by halfalogues and dialogues. For example, Emberson, Lupyan, Goldstein, and Spivey (2010; see also Galvan, Vessal, & Golley, 2013) found that ignoring a halfalogue as compared with a dialogue produced disruption to performance on a visual monitoring (tracking) task and a choice reaction task. While the existing evidence suggests that overhearing half of a cell-phone conversation is enough to reduce performance on a concurrent, attentionally-demanding task, there has been no attempt to investigate the potential impact of ignoring cell-phone conversations on the recall of complex visual information in more applied tasks such as following the witnessing of a (staged) crime.…”
mentioning
confidence: 99%